Prevalence of anaemia and visual impairment among primary school children of South Gujarat region of India: a cross sectional study - Pandya, Bharatkumar Balkrishna; Chaudhari, Upendrakumar Rameshbhai; Bhatt, Avirat A.; Thakor, Nilesh (International Journal of Contemporary Pediatrics, 2019)
Background: Nutritional Anemia and visual impairment among school age children are recognized as major public health problem in India. Authors objective was to study prevalence of anemia and visual impairment among school going adolescents of Vadodara and Surat city of Gujarat, India. Methods: This cross sectional study was carried during period from April 2015 to March 2016. Total 8 schools were selected from Vadodara and Surat city by purposive sampling. After taking the permission of principals of schools and informed written consent of the parents of children, 859 children from these schools were examined for anaemia and visual impairment. The data was collected by predesign, pretested proforma and analysed using SPSS version 17 (Trial version). Results: Out of total 859 children 421(49.1%) were female. Mean age of the study children was 8.95±1.52 years. The prevalence of anemia in children in present study was 61.6 % (529 children). The prevalence of anemia in female (274, 65.1%) was higher than males (255, 58.2%). Moderate visual impairment and blindness was 5.9% in girls and 8.2% in boys respectively. Severe visual impairment and blindness was 2.1% in girls and 2.7% in boys respectively and the gender difference was not statistically significant. Though 61(7.1%) children had moderate to severe visual impairment to blindness only 21 (2.4%) children were wearing spectacles. Conclusions: High prevalence of anaemia and visual impairment among these children needs great attention and health education.